100 facts on whales and dolphins - "Parker, Steve" (Miles Kelly Publishing Essex, 2006)
"100 Facts Whales & Dolphins" by Steve Parker, published by Miles Kelly Publishing in 2010. This 48-page children's book offers an engaging exploration into the world of whales and dolphins, presenting 100 facts accompanied by detailed illustrations and fun cartoons. The content is designed to educate young readers about these marine mammals, covering aspects such as their behaviors, habitats, and unique characteristics.